65 Proximal Lad PCI - Single Centre Long Term Outcomes 2003–2013. (31st May 2014) - Davison, BJ; Morley, R; Carter, J; de Belder, MA; Hall, JA; Muir, D; Swanson, N; Sutton, AGC; Wright, RA
Abstract : The 2010 ESC guidelines on myocardial revascularisation state that for patients with significant disease in the proximal LAD (pLAD), CABG is the preferred revascularisation strategy (class I, evidence Level A) and that PCI is less strongly supported (class IIa, evidence level B). The 2011 ACC/AHA guideline for PCI does not differentiate between modes of revascularisation for pLAD disease. We have analysed all PCI procedures performed at this institution between January 2003 and January 2013 with reference to involvement of the pLAD and long term outcome. In total 14, 935 PCI procedures were undertaken. We excluded 4, 080 emergency PCIs for STEMI. We present data for 10, 855 PCIs, 6, 859 for ACS patients and 3, 996 for patients with stable angina. Of these, 2, 723 (25%) involved the pLAD and 8, 132 (75%) non-pLAD disease (non-pLAD). Median follow up was 5.9 years, with 5 year follow up available for 6, 387. Patients with pLAD versus non-pLAD PCI were of similar age (median age 62 (IQR 54–72) vs 63 (IQR 56–71)) but more likely to be male (73% vs 71%, p = 0.04). pLAD patients were less likely to have had previous MI (22.5% vs 29.3%, p < 0.001), previous PCI (13.3% vs 18.6%, p < 0.001) or previous CABG (1.5% vs 11.2%, p < 0.001). Patients with pLAD disease were more likely to undergo multi vessel PCI (30.6% vs 16.1%, p < 0.001) or present with shock (0.8% vs 0.5%, p = 0.03). Use of DES was greater in the pLAD PCI group (77.8% vs. 66.8%, p < 0.001). Mortality rates at 1 and 5 years are shown in Table 1 . The data for repeat revascularisation are shown in Table 2 and are derived from data on patients returning to this hospital and do not include patients who may have attended a different cardiothoracic centre. Local geography means that this should be a small number. Conclusion: Our data suggest that the long term results for PCI to the pLAD are at least as good as the results for non-pLAD PCI. The rates of repeat revascularisation by PCI or CABG are markedly lower than in studies cited in the 2010 ESC revascularisation guideline which were mainly based on PCI by balloon angioplasty. The ESC guidelines are not based on contemporary outcomes of PCI for pLAD disease.